Outcomes of Arthroscopic Loose Body Management in Patella Instability: Medial Patellofemoral Ligament Neglect or Repair Versus Reconstruction. Issue 7 (31st July 2020) - Carroll, Alyssa; Pennock, Kristina Johnson Andrew
Objectives: Patellar instability is common in adolescents during their growth. Management of the actual patellar instability at the time of arthroscopic treatment for concomitant intra-articular loose body has been debated since many surgeons will manage first-time dislocations without surgery. To demonstrate that medial patellofemoral joint reconstruction, rather than neglect or repair of the ligament, should be performed at the time of arthroscopic loose body removal for first-time patellar instability events in children. Methods: Retrospective study design was performed on all patients who sustained a patellar instability event that resulted in an intra-articular loose body between 2011 and 2017 at our institution. Data was collected using ICD-9/10 and/or CPT codes. Patients included in the analysis were required to have a minimum of 24 month follow-up documented. We then performed chart review and radiographic review (XR and MRI). Variables collected included: demographics, weight, BMI, pain score, SANE score, Kujala score, subsequent recurrent instability, need for second surgery, growth plate status, trochlear dysplasia, TT-TG, Insall-Salvati ratio, and Blackburne-Peel ratio. Data analysis pooled the "neglect" and "repair" groups together and compared it to the "reconstruction" group. Continuous variables were examined for normal distribution and homogeneity and analyzed with ANOVA or Mann Whitney. Chi square was utilized for categorical variables. Results: 64 patients (34 males, 30 females) with a mean age at surgery of 14 years (range 9 to 18) met criteria. These participants had a reported mean weight (kg) and BMI of 67.6 kg and 23.9, respectively. In our two-cohort analysis, the reconstruction cohort demonstrated significantly less subsequent instability, with the rate of recurrence being 58.7% in the neglect/repair compared to 16.7% in the reconstruction group (p=0.002). In addition, the reconstruction group demonstrated significantly less patients that required second surgery (p=0.024). The only continuous variable that showed any statistically significant difference was the Insall-Salvati ratio (p=0.048) with the reconstruction group being a mean 1.3 versus a mean 1.4 in the neglect/ repair group. There was no difference was found for age, weight, BMI, Blackburn ratio, TDI, TT-TG, Pain, SANE, Kujala score, satisfaction, or length of follow-up. Conclusion: Medial patellofemoral ligament reconstruction in the setting of adolescent patellar instability with an intra-articular loose body results in significantly less recurrent instability and reduced need for subsequent surgery compared to those who do not undergo a concomitant ligament reconstruction.